CHARACTERISING STUDENTS’ PERSONAGE AND STUDENTS’ PERIOD IN THE WORLD LITERATURE - Abdullaeva , Nabiya (Zamonaviy filologiya muammolari, 2025)
The article is analyzed students’ personages as an object of real-life descriptions. Real life is a phrase used originally in literature to distinguish between the real world and fictional or idealized worlds, and in acting to distinguish be tween performers and the characters they portray. More recently, it has become a popular term on the Internet to describe events, people, activities, and interactions occurring offline; or otherwise not primarily through the medium of the Internet. It is also used as a metaphor to distinguish life in a vocational setting as opposed to an academic one, or adulthood and the adult world as opposed to childhood or adolescence.The article depicts the student's character in English literature. The role, genesis, national nature, poetic-typological features and the portrait of students in the works of English literary writers, their character’s features, similarities and differences.